Aging bones : a short history of osteoporosis - Grob, Gerald N., 1931-2015 (Johns Hopkins biographies of disease., 2014)
This book makes a historical inquiry into how the normal aging of bones was transformed into a medical diagnosis requiring treatment. -- Publisher description.